Análisis estético de las obras del surrealismo de Max Ernst como referente para una propuesta pictórica - Espinoza Obando, María Alexandra (2015)
In the present investigation an aesthetic analysis of works of surrealist artist Max Ernst, characterized in subjectively capture the unification of common knowledge and experimental is performed This research is executed by the information obtained from previous analyzes made by other authors, which were collected and applied through a qualitative study further the analytical and inductive reasoning methods allowed analyzing the information obtained and to subsequent the execution of works. The aesthetic components that Max Ernst plays in his works remain in effect and will be revisited in the course of the years by other artists to convey the reality around them from a different to the usual view, also the pictorial proposal aims to get attention of society in order to reach and disseminate relevant and take the issue and raised trend